A revision of Kerivoula hardwickii and occurrence of K. furva (Chiroptera: Vespertilionidae) in China - Yu, Wen-Hua; Li, Feng; Csorba, Gabor; Xu, Zhong-Xian; Wang, Xiao-Yun; Guo, Wei-Jian; Li, Yu-Chun; Wu, Yi (Zootaxa, 2018)
Although increased survey efforts using improved capture methods (particularly harp traps) have greatly expanded the quantity of Kerivoula specimens available in China, the understanding of the genus has been long constrained. After the recently published revision of the hardwickii-complex with the description of K. furva and re-evaluation of occurrence of K. titania in Taiwan, the critical overview of the previous data of Chinese Kerivoula (with the exception of K. picta, a strikingly colored and unmistakable species) is imperative. To clarify the taxonomy and distribution of the hardwickii-complex in China, 40 additional specimens collected from South China were studied through detailed morphological comparisons, multivariate statistical methods and phylogenetic inference. Our results evidently classified these specimens as K. furva instead of K. titania or K. hardwickii sensu stricto and together with the critical review of literature data indicate that all previous Chinese records of the two latter species were based on either misidentifications or outdated taxonomy. K. furva have so far been recorded in the Chinese provinces of Chongqing, Fujian, Guangdong, Guangxi, Hainan, Hunan, Jiangxi, Yunnan and Taiwan, but more field surveys are needed to confirm whether it could be found in other nearby provinces.